DISTANCE EDUCATION COMMUNICATIONS: THE SOCIAL PRESENCE AND MEDIA RICHNESS OF INSTANT MESSAGING - Kuyath, Stephen J.; Winter, Susan J. (Online Learning, 2006)
Instant messaging (IM) is changing the way we communicate with each other and may prove to be a more effective communication tool for distance learning environments than the more commonly used discussion groups and email. Media richness and social presence theories are described and young adults’ perception of IM’s richness and social presence are determined. In addition, preferences for using instant messaging for communicating messages of low, medium, and high levels of equivocality were investigated. The results indicate that young adults perceive IM to fall between email and the telephone in both social presence and media richness. As message equivocality increases, preference for the use of the telephone increases while preference for the use of email decreases. Preference for the use of IM increases for messages of intermediate equivocality, but decreases for those of high equivocality. Overall, young adults prefer IM over email as a communication tool, but prefer the phone over IM. Implications for media richness theory, social presence theory, and distance learning are described.